Ameloblastoma: A Clinical and Histopathological Study of 28 Cases Diagnosed in Benghazi - Elfergani , Marwa; Abd Alhamid Hamad, Mansora; El Maddani, Rehab; AL Jilali , Huda; Elmurtadi , Ali (Libyan Journal of Dentistry, 2022)
Aims: The study aims to describe the characteristics of of ameloblastoma in a retrospective sample of cases reported at the faculty of dentistry, University of Benghazi, Libya Methods A retrospective analysis of cases diagnosed with a ameloblastoma between 2001 and 2016 at faculty of dentistry -Benghazi-libya were reviewed histologically. The cases were then subclassified according to the basic criteria of the World Health Organization. In addition, cases were analysed in terms of clinicopathologic and histopathologic features. Results: A total of 28 ameloblastomas types were identified: 8 conventional, 2 peripheral, and 17 unicystic (4 cases ameloblastoma arising in dentigerous cysts) and 1 case is malignant ameloblastoma. Tumours were distributed throughout the jaws with 26 cases in mandibular, 2 cases in maxilla, (2 cases and cross midline, and 2 cases in an anterior location). Conclusion: The clinical epidemiological profile of the patients from the present study is very similar to other populations with regards to gender, age and tumor location, with unicystic ameloblastoma being the most common subtype in our population, in contrast to other reports.